Sustainable Tourism and the Intention of Generation Z to Choose Sustainable Tourism (International Journal of Scientific Research and Management (IJSRM), 2024)
Sustainable tourism development is one of the sustainable development orientations. Sustainable tourism development can be impacted by promoting increased interest in and selection of sustainable tourism destinations. This study aims to clarify the concept of sustainable tourism, examining the current factors influencing the intention to choose sustainable tourism. The subjects of the study are young people of Generation Z, in order to enhance and promote the travel intentions of this potential target group in the future. Based on survey data collected from 314 Gen Z travelers, the factors affecting Gen Z’s intention to choose sustainable tourism in Vietnam are clarified.